Code Mixing in Reizuka Ari’s TikTok Vlogs: An Analysis of Indonesian–English Language Use - Nita Fauziah (Jurnal Dieksis ID, 2026)
This research is urgent because analyzing code mixing in Reizuka Ari’s TikTok vlogs reveals how Indonesian–English language use on social media shapes contemporary communication practices and youth linguistic identity. This research is motivated by the phenomenon of Digital Multilingualism in the digital era which has transformed social media into a space for identity negotiation through the use of language..The purpose of this study is to identify and classify Indonesian-English code mixing patterns in Reizuka Ari's TikTok vlog..Using a descriptive qualitative method with Muysken's theoretical framework, this study analyzed 15 speech data from the video "SPILL RUMAH REIZUKA ARI".The results of the data analysis show that code mixing practices are dominated by the Insertion type at 53.33% (8 data), followed by Alternation at 26.66% (4 data), and Congruent Lexicalization at 20.01% (3 data). The dominance of the Insertion type can be seen in the use of single words or phrases such as " before ", " literally ", and " dream house " which are inserted without changing the basic structure of the Indonesian sentence. Another unique finding shows the existence of deep morphological integration through the provision of Indonesian affixes to foreign words, such as in the words " heels " and " cealing ".The conclusion of this study confirms that in spontaneous digital communication, language boundaries become very flexible and the use of mixed languages ??has become a new communicative competence to maintain the relevance and attractiveness of content in cyberspace.